2021
DOI: 10.1186/s13075-021-02599-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns in rheumatoid arthritis patients newly initiated on biologic and conventional synthetic disease-modifying antirheumatic drug therapy and enrolled in a North American clinical registry

Abstract: Background Understanding the evolving treatment patterns in patients with rheumatoid arthritis (RA) is important for rheumatologists to make the best practice decisions and optimize treatment. Here, we describe treatment patterns among patients newly initiated on biologic and/or nonbiologic RA therapy over time after enrollment in the US Corrona RA registry. Methods This was a retrospective, cohort study of adult patients with RA enrolled in the Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
3
15
0
Order By: Relevance
“…The trend of decreasing therapy duration was observed also in recent work by Mease et al (23), although they used data of patients enrolled in the CorEvitas RA registry between 2004 and 2015 and studied a smaller set of therapies. There exist some studies that have tried to describe sequential therapies using Sankey diagrams (12,13).…”
Section: Discussionsupporting
confidence: 60%
“…The trend of decreasing therapy duration was observed also in recent work by Mease et al (23), although they used data of patients enrolled in the CorEvitas RA registry between 2004 and 2015 and studied a smaller set of therapies. There exist some studies that have tried to describe sequential therapies using Sankey diagrams (12,13).…”
Section: Discussionsupporting
confidence: 60%
“…Second, the number of patients starting TNFi in monotherapy was relatively small and represented only 11.5%. Other registries indicate that bDMARDs alone can be given in 30–50% [ 35 , 36 ]. Our smaller proportion of monothorapy might reflect the compliance efforts of physicians working within the ATTRA registry; but, on the other hand, we do not have the reliable data to verify the actual pick-up of csDMARDs in pharmacies, not to mention the gap in the verification of patients compliance with their use at home.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 In a North American clinical registry study comprising 8027 COHORTs of RA, it was observed that patients who initiated therapy with conventional synthetic DMARDs monotherapy had low disease activity when compared with those who were initiated with biologics. 10 It had been reported that patients with low disease activity had less chance of developing cerebral vasculitis. Glucocorticoids constituted an effective treatment for CNS rheumatoid vasculitis.…”
Section: Discussionmentioning
confidence: 99%